COMPARATIVE MORPHOLOGY OF THE NERVOUS SYSTEM OF THE LIVER OF MAMMALS WITH DIFFERENT TYPES OF FOOD. - Dilfuza S. Shodiyarova (TADQIQOTLAR, 2025)
ABSTRACT This article analyzes the scientific literature on the study of the nervous system of  the  liver  of  mammals  with  different  types  of  food  and  describes  the  unexplored aspects of this problem. 10 rabbit livers representing herbivore mammals and 10 dog livers  representing  carnivore  mammals  were  taken  for  study.  The  results  of  the research  revealed  that  the  nervous  system  of  the  liver  of  mammals  has  specific morphofunctional properties depending on the type of food.